Bicultivo de folhosas consorciadas com beterraba em função de adubação com flor- de-seda e densidades populacionais - Andrade Filho, Francisco Cicupira de (2012)
This study aimed to assess the agroeconomic viability of the Bicropping of leafy vegetables intercropped with beet as a function of the fertilization with rooster tree and population densities of the component crops. The study was conducted during the period June to November 2011, at the Experimental Farm 'Rafael Fernandes' of the Universidade Federal Rural do Semi-Árido (UFERSA), located in the district of Alagoinha, 20 km away from the city of Mossoró-RN. The experimental design was a randomized complete block with treatments arranged in a 4 x 4 factorial, with four replications. The treatments consisted of combinations of four amounts of rooster tree incorporated into the soil (6, 19, 32 and 45 t ha-1 on a dry basis) with four population densities combinations of component crops (20C-50B-20A%, 30C-50B-50A%, 40C-50B-40A% and 50C-50B-50A% of the recommended densities in sole crop - RDSC, where C = Coriander, B = Beet and A = Arugula). In the cultures of coriander and arugula, the following characteristics were evaluated: plant height, number of leaves per plant or number of stems per plant, yield of green mass and dry mass of shoots. In beet, evaluations were made for plant height, number of leaves per plant, dry mass of shoot, total yield, commercial yield, root dry mass and classified yield of roots. In the intercropping systems, evaluations were made for the canonical variable, productive efficiency index, gross income, net income, rate of return and profitability index. The best productive performance of coriander (1.57 t ha-1) was obtained in the population density of 40C-50B-40A in the amount of 18.60 t ha-1 of rooster tree added to the soil. Best yield performance of arugula (8.21 t ha-1) was obtained in the population density of 40C-50B- 40A in the amount of 10.26 t ha-1 of rooster tree incorporated into the soil. The highest commercial and total yields (18.41 and 16.97 t ha-1) of beet were gotten in the population density of 40C-50B-40A in the amounts of 27.82 and 27.49 t ha-1 of rooster tree, respectively, added to the soil. Both in the multivariate method as in univariate method were registered significant interactions between the treatment-factors studied. Optimization of economic indicators was obtained in the density of 30C-50B-30A in the amount of rooster tree of 32 t ha-1 or in the density of 20C-50B-20A in the amount of 45 t ha-1of rooster tree incorporated into the soil